Role of Ceramides in the Molecular Pathogenesis and Potential Therapeutic Strategies of Cardiometabolic Diseases: What we Know so Far - Shalaby, Youssef M.; Al Aidaros, Anas; Valappil, Anjana; Ali, Bassam R.; Akawi, Nadia (Frontiers in Cell and Developmental Biology, 2022)
Ceramides represent a class of biologically active lipids that are involved in orchestrating vital signal transduction pathways responsible for regulating cellular differentiation and proliferation. However, accumulating clinical evidence have shown that ceramides are playing a detrimental role in the pathogenesis of several diseases including cardiovascular disease, type II diabetes and obesity, collectively referred to as cardiometabolic disease. Therefore, it has become necessary to study in depth the role of ceramides in the pathophysiology of such diseases, aiming to tailor more efficient treatment regimens. Furthermore, understanding the contribution of ceramides to the pathological molecular mechanisms of those interrelated conditions may improve not only the therapeutic but also the diagnostic and preventive approaches of the preceding hazardous events. Hence, the purpose of this article is to review currently available evidence on the role of ceramides as a common factor in the pathological mechanisms of cardiometabolic diseases as well as the mechanism of action of the latest ceramides-targeted therapies.